Consensus guidelines on the diagnosis and management of myasthenia gravis by the Saudi Arabia Neuromuscular and Electrodiagnostic Medicine and neuromuscular specialists from the Gulf Cooperation Council region - Ali Mohammed Alshehri; Mohammed H. Alanazy; Majed Alabdali; Ahmad R. Abuzinadah; Aysha Alshareef; Ahmad Abulaban; Raed A. AlRoughani; Fatema Mohamed Abdulla; Ali M. A. Hassan; Mohammed Ibrahim Alhatou; Abubaker Almadani; Suhail Abdulla Alrukn; et al. (Therapeutic Advances in Neurological Disorders, 2025)
The introduction of numerous therapeutic advancements in the management of myasthenia gravis (MG) may add difficulties in clinical decision-making, especially when no recommendations tailored to the local context are available. For this reason, the Saudi Arabia Neuromuscular and Electrodiagnostic Medicine (SANEM) chapter of the Saudi Neurology Society launched an initiative to discuss and agree on issues related to the management of MG in the Gulf Cooperation Council (GCC) region. An expert panel from all GCC countries (Saudi Arabia, United Arab Emirates, Bahrain, Kuwait, Qatar, and Oman) was formed to develop practical recommendations using the Delphi method to facilitate the management approach of MG and enhance patient outcomes.